Re-Innovation from Failure, Institutional Environmental Differences, and Firm Performance: Evidence from China - Zhuang Xiong; Pengju Wang; Yu Zhao (Amfiteatru Economic)
Due to an anti-failure bias, theoretical and practical studies have not focused much on the problem of innovation failure. The literature does not include studies on how the effect of re-innovation input on firm performance can still be explained by existing theories, especially in the case of previous innovation failures. To explore the intrinsic relationship between the re-innovation from failure and firm performance, as well as the influencing mechanism of the institutional environment differences on a firm’s re-innovation activities, using the data of the Listed Companies in China’s pharmaceutical manufacturing industry from 2008 to 2014 and a multiple regression model, the relationships between the reinnovation from failure, institutional environment differences, and firm performance were analyzed from 3 aspects: government intervention, financial development, and legal environment. The results show that the re-innovation input from failure has a significant positive impact on firm performance. The level of government intervention and the level of financial development play significant negative and positive moderating roles in the relationship between the re-innovation input and firm performance, respectively, and the above-mentioned effects are more prominent in eastern China. Moreover, with the improvement of the marketization of the financial industry, the beneficial effect of the reinnovation input from failure on firm performance in state-owned firms will be further strengthened. However, the moderating effect of the legal environment is not obvious.